FINANCIAL STATEMENTS ANALYSIS AND FIRMS’ VALUATION IN VIETNAM - Kim, Trang Thu (2009)
Valuation is the central focus in fundamental analysis. This dissertation considers the usefulness of financial statements in predicting market values of companies in Vietnam stock market by adopting the valuation model constructed by Chung et al., (2001). The overview of Vietnam stock market; some definitions about financial statements, valuation; description of several basis valuation models and empirical evidence including the description of valuation model developed by Chung et al., (2001) are examined. Investigation of using financial statements in forecasting Vietnamese companies’ intrinsic values are discussed by dividing the sample into 3 periods of time: estimation period, prediction period and holding period. After estimating the empirical regression model to determine whether the stocks are overvalued or undervalued, a series of trading strategies with zero net investment (D-portfolios) is built up. The results of the study show that the business valuation model built up by Chung et al., (2001) can be effectively applied to the Vietnam stock market and the financial statements are useful in predicting the market prices of stocks to some extent and the D-strategy can be created in order to support investors in their investment decision making in Vietnam. This may be interest to not only analysts but also investors in other emerging markets where the stock markets have similar characteristics as Vietnam does.